Hubungan Insentif Pajak dengan Iklim Investasi bagi Perusahaan Penanaman Modal Asing di Sektor Industri Tekstil di Indonesia - HArtoNo, M. EDi; SEtYoWAti, MiLLA SEPLiANA (UI Scholars Hub, 2011)
This quantitative research relates tax-incentive policy with investment-climate for foreign-invested companies in textile industry by using the method of survey analysis. This research took samples by using simple random sampling method. The result shows that the tax-incentive policy is not significantly related to investment-climate of foreign-invested companies in textile industry in Indonesia. There are a lot of factors that influence investment-climate, among others, the availability of cheap, professional experts, political stability, the condition of market and its potential, macro-economic stability, the condition of infrastructure, legal certainty, and the condition of bureaucracy, as well as the rate of corruption in Indonesia. Based on the analysis on the research result, however, market access appears to be the significant factor that generates foreign investors in textile industry in Indonesia.